2018
DOI: 10.1002/ncp.10198
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength, but Not 5‐Meter Walk, Adds Value to a Clinical Nutrition Assessment

Abstract: Background: Decreased physical functioning is associated with malnutrition and common in acute care patients; determining loss of function is often considered part of a comprehensive nutrition assessment. Handgrip strength (HGS) and 5-meter timed walk (5m) are functional measures used in a variety of settings. This analysis sought to determine which functional measure could be added to a hospital nutrition assessment, based on its feasibility and capacity to discriminate patient subgroups. Methods: Eligible me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
13
2
2
Order By: Relevance
“…Another study including 1250 patients showed that malnourished (SGA-B or SGA-C) patients had significantly lower HGS; however, they also noted that HGS is not an accurate screening tool for malnutrition. 27 Although HGS is significantly associated with SGA, HGS showed poor validity as a single nutrition indicator in the majority of cited studies, 13,26,27 as demonstrated in the current study. Therefore, HGS as an isolated measure for malnutrition diagnosis does not seem to yield accurate results.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Another study including 1250 patients showed that malnourished (SGA-B or SGA-C) patients had significantly lower HGS; however, they also noted that HGS is not an accurate screening tool for malnutrition. 27 Although HGS is significantly associated with SGA, HGS showed poor validity as a single nutrition indicator in the majority of cited studies, 13,26,27 as demonstrated in the current study. Therefore, HGS as an isolated measure for malnutrition diagnosis does not seem to yield accurate results.…”
Section: Discussioncontrasting
confidence: 48%
“…In a cross‐sectional study with a sample of 668 adult patients, Guerra et al 13 also showed a weak correlation between PG‐SGA score and HGS values ( r = −0.290; P < .001). Another study including 1250 patients showed that malnourished (SGA‐B or SGA‐C) patients had significantly lower HGS; however, they also noted that HGS is not an accurate screening tool for malnutrition 27 . Although HGS is significantly associated with SGA, HGS showed poor validity as a single nutrition indicator in the majority of cited studies, 13,26,27 as demonstrated in the current study.…”
Section: Discussioncontrasting
confidence: 47%
“…40 Although finding a significant association between grip strength and nutritional status, McNicholl described grip strength as having "poor validity as a single nutrition indicator". 41 As more of the patients they tested completed a grip strength assessment (92%) than a 5 meter walking assessment (43%), they concluded that grip strength "is a more useful functional measure" than the 5 meter walk test.…”
Section: Grip Strength As a Biomarker Of Current Statusmentioning
confidence: 99%
“…Examining a sample of older Chinese inpatients who were tested upon admission, Zhang et al noted that those with lower grip strength were at greater risk of malnutrition, as measured by nutritional risk screening and subjective comprehensive assessment [ 46 ]. McNicholl found a significant association between grip strength and nutritional status, but indicated that grip strength “has little validity as a single nutritional indicator” [ 47 ]. Since more tested patients completed the grip strength assessment (92%) than the 5-m walk assessment (43%), they concluded that grip strength is "a more useful functional indicator" than the 5-m walk test [ 47 ].…”
Section: Discussionmentioning
confidence: 99%